Resilience Serves as a Protection Against Depression and Sleep Problems among Hemodialysis Nurses in Indonesia - Tri Hapsari Retno Agustiyowati; Linlin Lindayani; Susi Kusniasih (Journal of Health Sciences and Medical Development, 2026)
Nurses are vital in managing infectious disease outbreaks, yet prolonged exposure to high-stress environments, such as during the COVID-19 pandemic, can impair their sleep and increase depressive symptoms, potentially weakening psychological resilience. This study examined the relationships between sleep disturbances, depressive symptoms, and resilience among nurses working in hemodialysis units in post-pandemic Indonesia. Registered nurses having at least a year of clinical experience participated in a cross-sectional survey that was carried out in West Java between April and June 2023.  The Zung Self-Rating Depression Scale (SDS), the Insomnia Severity Index (ISI), and the Connor-Davidson Resilience Scale (CD-RISC) were among the tools used. Mediation analysis using bootstrapping was performed to assess whether resilience mediated the association between sleep disturbances and depressive symptoms. A total of 180 valid responses (76.5% response rate) were analyzed. Most participants (58.33%) held a nursing diploma; only 7% were married. Results showed that both the direct relationship between sleep problems and depressive symptoms and the indirect path via resilience were significant. The direct effect explained 43.21% of the total variance, while indirect effects accounted for 34.17%, with resilience specifically mediating 13.21%. Resilience significantly buffers the negative impact of sleep disturbances on depressive symptoms among hemodialysis nurses. Promoting resilience through targeted interventions could enhance psychological well-being and sleep quality, especially in high-stress clinical environments.